Effects of exchange rate volatility on Brazilian exports - Pianca, Osmar José Bertholini; Campani, Carlos Heitor d'Avila Pereira; Cardoso, Rafael (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
An economy with high exchange rate volatility brings uncertainties to its international trade flow and, therefore, affects its country’s exports. Such uncertainties justify researches trying to identify the effects of exchange rate volatility on exports. This paper aims to investigate the effects of the US dollar exchange rate volatility on Brazilian exports with a focus on certain relevant sectors of Brazil’s economy. Four different metrics of exchange rate volatility were used as independent variables whereas the exported volumes of some products and sectors were taken as dependent variables. The estimation process was carried out by means of the Generalized Method of Moments because it presents better properties for finite samples and it treats the endogenicity problem. The results show that some products and sectors are indeed affected by volatility of the US dollar exchange rate in a negative way, while other products and sectors seem to have not been affected.